Requirements of stress tests model and the possibility to apply in Iraqi banks exploratory study of the views of a sample of staff in the central Bank of Iraq . - امين, صلاح الدين محمد; الشمري, صادق راشد (Journal of Economics and Administrative Sciences, 2013)
Abstract This research attempt to explain the essential aspects of one important model in management of Bank risks , that is (stress testing) , which increase the concentrate on it resulting the negative affects of Global financial crisis that it accuar in 2008 to study the application possibilities in iraqian banks to enhancing the safety and financial soundness Becuase the classical tools  in Risk management don’t give clear image on Banks ability  in facing risks, hence the Basel committee on Banking supervision focusing in agreement of Basel 2,3 on stress testing when it doing the internal capital adequacy assessment process (ICAAP) .To achieving the reseach objectives we chocing sample from employer and managers in Iraqi centeral Bank to identify their point view in application possibilities of stress testing in Iraqi Banks through questionneir prepare fore this purpose .The research Based on primary hypothesis (uses of stress testing affect in management of bank risks and capital allocation ) .Many nonparametric statistic tools uses and standard deviation and (t test) to analyze the sample answers and test the hypothesis , the research arrive that iraqian banks needed stress testing tools to risk management and facing unexpected risk then we recomeded to adaptation stress testing as importance tool in risk management and as one of modern Early warning devices through scenarios stsuctured to this purpose .